2017
DOI: 10.3390/antibiotics6010005
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin Increases Heart Rate in Humans

Abstract: (1) Background: We assessed the effect of moxifloxacin on heart rate, and reviewed the heart rate effects of other antibiotics; (2) Methods: A total of 335 normal volunteers had 12-lead electrocardiograms recorded at multiple time points before and during treatment with moxifloxacin and with placebo in seven consecutive, thorough QT studies of crossover design; (3) Results: The average baseline heart rate across the seven studies was 61.5 bpm. The heart rate after moxifloxacin dosing was analyzed at five time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Shorter MDR-TB regimen contains various drugs which can lead to various cardiovascular autonomic adverse drug reactions like, moxifloxacin causes QT prolongation and increased heart rate; kanamycin causes increased heart rate; ethionamide causes postural hypotension; clofazimine causes torsade-de-points; ethambutol causes myocarditis and pericarditis. 8,10,[16][17][18][19] These adverse drug reactions can lead to sudden cardiac death. But, there is paucity of data regarding, effect of MDR-TB on ANS and effect of shorter MDR-TB regimen drugs on ANS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shorter MDR-TB regimen contains various drugs which can lead to various cardiovascular autonomic adverse drug reactions like, moxifloxacin causes QT prolongation and increased heart rate; kanamycin causes increased heart rate; ethionamide causes postural hypotension; clofazimine causes torsade-de-points; ethambutol causes myocarditis and pericarditis. 8,10,[16][17][18][19] These adverse drug reactions can lead to sudden cardiac death. But, there is paucity of data regarding, effect of MDR-TB on ANS and effect of shorter MDR-TB regimen drugs on ANS.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs individually cause many adverse drug reactions like, increase in heart rate, postural hypotension, peripheral neuropathy, QT prolongation, optic neuropathy, hearing loss, seizures and headache. [7][8][9][10][11] So, these drugs affects both central nervous system (CNS) as well as peripheral nervous system (PNS). 7 So, by HRV measurement it can be correlated that whether these adverse drug reactions are due to ANS dysfunction or not.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling predicts a maximum increase at steady state of 8.0 bpm in patients receiving the clinical dose of 1,000 mg b.i.d., although previous studies with less robust ECG did not show an increase in HR. At least six other macrolide and fluoroquinolone antibiotics are known to increase HR . Although increase in HR was observed with these antibiotics at supratherapeutic levels, none of them manifested any serious adverse events when administered to infected patients at their therapeutic doses.…”
Section: Discussionmentioning
confidence: 99%
“…10 Ultimately, human health will be affected by these antibiotic residues through the ecological cycle and food chain accumulation, as a consequence of which, the environmental surveillance of antibiotics is of great importance for the protection of human, animal and ecosystem health. 11,12 Moxi-oxacin (MFX), a uoroquinolone antibiotic, can be used to treat pneumonia, skin and skin structure infections, and increases heart rate in humans, 13 but a survey also showed that MFX can induce tinnitus in older adults. 14 Therefore, it is very necessary to establish an effective MFX determination method, especially for the analysis of MFX content in food and water.…”
Section: Introductionmentioning
confidence: 99%